Music therapy in children's hospices : Jessie's Fund in action - Pavlicevic, Mercedes; Wood, Victoria, 1953-2016 (Jessica Kingsley Publishers, 2005)
The use of music therapy in children's hospices is burgeoning. This moving and extremely helpful text brings together the experiences of eleven music therapists working with children who are in the final stages of life-limiting illness. The contributors discuss the adaptation of the therapy to the hospice environment and to the individual needs of the patient. They explore the key concerns of all practitioners in this field such as how to empower the patient, how to help bereaved siblings and how the therapists themselves can find support. The volume takes a holistic approach to children's hos.